Metabolic normality in overweight and obese subjects. Which parameters? Which risks - Pataky, Z; Makoundou, V; Nilsson, P; Gabriel, R.S; Lalic, K; Muscelli, E; Casolaro, A; Golay, A; Bobbioni-Harsch, E (International Journal of Obesity, 2011)
Objectives: The objective of this study was to define metabolic normality and to investigate the cardiometabolic profile of metabolically normal obese. Design: Cross-sectional study conducted at 21 research centers in Europe. Subjects: Normal body weight (nbw, n=382) and overweight or obese (ow/ob, n=185) subjects free from metabolic syndrome and with normal glucose tolerance, were selected among the Relationship between Insulin Sensitivity and Cardiovascular Disease study participants. Main outcome measures: Insulin sensitivity was assessed by the clamp technique. On the basis of quartiles in nbw subjects, the limits of normal insulin sensitivity and of normal fasting insulinemia were established. Subjects with normal insulin sensitivity and fasting insulin were defined as metabolically normal. Results: Among ow/ob subjects, 11% were metabolically normal vs 37% among nbw, P<0.0001. Ow/ob subjects showed increased fasting insulin (P=0.0009), low-density lipoprotein cholesterol (LDL-cholesterol) (P=0.004), systolic (P=0.0007) and diastolic (P=0.001) blood pressure, as compared with nbw. When evaluating the contribution of body mass index (BMI), hyperinsulinemia and insulin resistance, BMI showed an isolated effect on high-density lipoprotein (P=0.007), high-sensitivity C-reactive protein (P<0.0001), systolic (P=0.002) and diastolic (P=0.008) blood pressures. BMI shared its influence with insulinemia on total cholesterol (P=0.04 and 0.003, respectively), LDL-cholesterol (P=0.003 and 0.006, respectively) and triglycerides (P=0.02 and 0.001, respectively). Conclusion: In obese subjects, fasting insulin should be taken into account in the definition of metabolic normality. Even when metabolically normal, obese subjects could be at increased risk for cardiometabolic diseases. Increased BMI, alone or with fasting insulin, is the major responsible for the less favorable cardio-metabolic profile.